A Study on the Gaseous Benzene Removal Based on Adsorption onto the Cost-Effective and Environmentally Friendly Adsorbent - Isinkaralar, Kaan (MDPI AG, 2023)
Removal of benzene is essential for human and environmental health because it has toxic and hazardous properties at various concentrations. Theseneed to be effectively eliminated with carbon-based adsorbents. PASACs, carbon-based adsorbents obtained from using the needles of Pseudotsuga menziesii, were produced by optimized HCl- and H2SO4-impregnated approaches. Regarding physicochemical structure, the optimized PASAC23 and PASAC35 with surface areas of 657 and 581 m2/g and total pore volumes of 0.36 and 0.32 cm3/g showed ideal temperatures of 800 °C. In order to investigate and compare internal benzene removal efficiency, PASAC23 and PASAC35 were studied separately. Initial concentrations were found to range from 5 to 500 mg/m3, and between 25 and 45 °C. The removal rate of benzene by PASAC23 and PASAC35 was 97 and 94% at low concentrations, respectively. While the highest capture amount for PASAC23 and PASAC35 was found to be at 25 °C with 141 and 116 mg/g, the adsorption capacity decreased to 102 and 90 mg/g at 45 °C. The holding capacity decreased between 22.41 and 27.66% due to increasing temperatures. After five cycles of PASAC23 and PASAC35 regeneration, we found that they could remove 62.37 and 58.46% of benzene, respectively. These results confirmed that PASAC23 is a promising environmentally adsorbent for effectively removing benzene with a competitive yield.
Keywords: gas treatment; QD241-441; reversible adsorption; Organic chemistry; air pollutants; sustainable porous carbons; air pollutants; gas treatment; environmental protection; reversible adsorption; sustainable porous carbons; environmental protection; Article